2017
DOI: 10.3390/su9040613
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Wind and Wave Energy Assessment around Malè and Magoodhoo Island (Maldives)

Abstract: Abstract:The Maldives are situated in the remote equatorial Indian Ocean, covering 900 km from north to south. The 26 coral atolls forming the archipelago are composed of sand and coral with a maximum height of about 2.30 m above the mean sea level. Periodic flooding from storm surges and the frequent freshwater scarcity are perceived by the population and the economic operators as the major environmental stresses. Moreover, the strong dependence on imported fossil fuels increases, even more, the environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 87 publications
1
37
0
Order By: Relevance
“…However, Contestabile et al indicated that economic and environmental analyses, generally speaking, should refer to real produced energy and not to theoretically produced energy. This potential produced energy takes into account wave-to-wire efficiency or wind-to-wire efficiency [47]. Therefore, in this paper, we considered an average efficiency of the three WECs and an average efficiency of the wind generator and calculated the potential produced energy for wave energy (E wec_mean , unit: kWh/km/a) and wind energy (E turb_mean , unit: kWh/km 2 /a).…”
Section: ) Overall Condition Analysis For Wave and Wind Energymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Contestabile et al indicated that economic and environmental analyses, generally speaking, should refer to real produced energy and not to theoretically produced energy. This potential produced energy takes into account wave-to-wire efficiency or wind-to-wire efficiency [47]. Therefore, in this paper, we considered an average efficiency of the three WECs and an average efficiency of the wind generator and calculated the potential produced energy for wave energy (E wec_mean , unit: kWh/km/a) and wind energy (E turb_mean , unit: kWh/km 2 /a).…”
Section: ) Overall Condition Analysis For Wave and Wind Energymentioning
confidence: 99%
“…Therefore, in this paper, we considered an average efficiency of the three WECs and an average efficiency of the wind generator and calculated the potential produced energy for wave energy (E wec_mean , unit: kWh/km/a) and wind energy (E turb_mean , unit: kWh/km 2 /a). For a generic WEC, the overall averaged efficiency was 16.5%, and the maximum energy derived from a wind generator was only 59% of the available wind kinetic energy [47]. Based on 38 years of recent ERA-Interim data, the theoretically produced energy and the potential produced energy for wave and wind energy were calculated for the 3 key stations.…”
Section: ) Overall Condition Analysis For Wave and Wind Energymentioning
confidence: 99%
“…where m −1 stands for the minus-one spectral moments, m 0 stands for the zeroth spectral moments [28,29]. The input and output power of the hydraulic system can be calculated by Equations (3) and (4) respectively:…”
Section: Power Curvesmentioning
confidence: 99%
“…The most widely deployed marine energy source worldwide is offshore wind energy, although Elliott et al designated the availability of wind energy to be moderate for large‐scale conversion in the Maldives. Contestabile et al performed a wind and wave energy assessment around two locations in the Maldives. The annual offshore wave power was found to range between 8.46 and 12.75 kW/m, while the 10‐ and 100‐m mean wind power density is respectively 0.08 and 0.16 kW/m 2 .…”
Section: Introductionmentioning
confidence: 99%